2018
DOI: 10.2147/copd.s163795
|View full text |Cite
|
Sign up to set email alerts
|

COPD affects worker productivity and health care costs

Abstract: PurposeThis study aimed to measure the true burden of COPD by calculating incremental direct and indirect costs. Direct medical resource use, productivity metrics, and COPD-specific resource use and costs were also evaluated.Patients and methodsThis was a retrospective, observational, matched cohort study using administrative claims data from the Truven Health MarketScan® Commercial Claims and Encounters and the Health and Productivity Management databases (2007–2010). Working-age (18–65 years) patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 22 publications
3
38
0
1
Order By: Relevance
“…Due to smoking and increasing air pollution the current prevalence of 10.1% is estimated to further increase in the next decades (Celli and Wedzicha, 2019). Considering the enormous medical and financial burden of COPD (May and Li, 2015;Patel et al, 2018), there is a need to develop efficient biomarker-based diagnostics, and molecularly defined therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Due to smoking and increasing air pollution the current prevalence of 10.1% is estimated to further increase in the next decades (Celli and Wedzicha, 2019). Considering the enormous medical and financial burden of COPD (May and Li, 2015;Patel et al, 2018), there is a need to develop efficient biomarker-based diagnostics, and molecularly defined therapies.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that about 3 million people dead from COPD every year [3,31]. Patel JG et al showed that COPD caused average of 5 more days of work absence and $641 short-term disability associated extra costs each year in the USA [32]. It was estimated that the global years lived with disability (YLDs) of COPD was about 29.4 million in 2010 [33].…”
Section: Discussionmentioning
confidence: 99%
“…COPD exacerbations are responsible for the majority of the substantial burden that COPD places on healthcare systems [2,3]. In the USA, the annual cost of COPD management has been shown to increase proportionally with the number of COPD exacerbations, with COPDrelated costs, including pharmacy claims for COPD treatments, more than six times higher in patients experiencing frequent (≥2/year) exacerbations ($4361) compared with those who had none ($644) [4].…”
Section: Introductionmentioning
confidence: 99%